Liquefaction potential analysis of reusep prestress bridge in Pidie jaya due to 6.4 mw earthquake - R. P., Munirwan; M., Munirwansyah; K., Jamaluddin; H., Gunawan; A. Z., Mubarak; Putra Jaya, Ramadhansyah; Duraisamy, Youventharan (2019)
Pidie Jaya is one of the districts in Aceh Province – Indonesia. On December 7, 2016, Pidie Jaya experienced a shallow 6.4 Mw earthquake which destroyed some vital buildings and also human loss. Based on preliminary field investigation, some geological damages like soil movement, soil cracks, and liquefactions occur because of the earthquake. Some liquefaction phenomena scattered in the area of Ulim, Panteraja, Meunasah Balek, Manohara Beach and Sagoe Trienggadeng. An evidence of liquefaction in Pidie Jaya area was displayed in this research based on several literature review. Furthermore, these paper aims to identify liquefaction possibilities in Trienggadeng Reusep Prestress Bridge based on a geotechnical investigation of N-SPT and some seismic data by using Kishida method. The surrounded area of the bridge was first evaluated in terms of geological setting, tectonics and seismic activity related to 6.4Mw of the previous earthquake. Furthermore, it was found from the soil profile that the studied area has a potency of liquefaction because of several saturated sand layers and high groundwater level. Effective overburden pressure of sand layers was calculated and plotted with N-SPT value to determine the possibility of liquefaction. The result shows that liquefaction potential shows high possibility for sand dominant layers both from bor-log 1 in 17.5 m and 25 m depths, and bor-log 2 in the depth of 17 m and 26.5 m.